500 years of Karagöz (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
This article is a reflection about Turkish Shadow Theatre, Karagöz Theatre.It presents Karagöz techniques; the structure of Karagöz plays and the main characters, providing the reader with a clear view of Karagöz Shadow Theatre, an art form that will complete its 500th birthday in 2017.Keywords: Turkish shadow theatre. Karagöz theatre. Theatre History.